Increased arterial stiffness in childhood onset diabetes: a cardiovascular magnetic resonance study. (25th July 2017) - Heier, Martin; Stensæth, Knut Haakon; Brunborg, Cathrine; Seljeflot, Ingebjørg; Margeirsdottir, Hanna Dis; Hanssen, Kristian F; Dahl-Jørgensen, Knut
Abstract: Aims: Arterial stiffness is a strong predictor of cardiovascular events. We aimed to assess the impact of type 1 diabetes (T1D) on arterial stiffness and cardiac function in young adults. Methods and results: Aortic pulse wave velocity (PWV), distensibility, left ventricular (LV) function and LV mass were measured by cardiovascular magnetic resonance imaging (CMR) in 47 T1D patients and 33 healthy controls. All were participants in the Atherosclerosis and Childhood Diabetes study, with baseline values registered 5 years previously. The patients had a mean age of 20.8 years and a median duration of diabetes of 10.0 years. PWV was significantly higher in the diabetes group compared with controls, mean 4.10 (SD = 4.58) vs. 3.90 (SD = 4.04) m/s, P  = 0.045. In the diabetes group, insulin pump users at baseline had lower PWV than multiple injection users, mean 3.94 (SD = 0.38) vs. 4.23 (SD = 0.48) m/s, P  = 0.028. Also in the diabetes group, multiple regression analysis identified C-reactive protein (CRP), female gender and insulin pump use as independent baseline risk factors for PWV 5 years later. There was no difference in cardiac function or LV mass between the diabetes and control groups. Conclusion: In this prospective study, we found increased PWV assessed by CMR in young adults with T1D compared with controls. Also, CRP, female gender and insulin pump use emerged as independent baseline risk factors for PWV 5 years later.